Science Process Skills of Grade VI Elementary Students in Object Changing Material - Winarni, Neni; Sopandi, Wahyu; Sujana, Atep; Muharam, Agus (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Science Process Skills (SPS) are all scientific skills used to acquire, develop, and apply scientific concepts and theories. SPS mastery is not only useful in science learning but also for students' daily lives. Therefore mastery of abilities is very important in the science process since elementary school age. This study aims to obtain an overview of the profile of students' science process skills. The research method used was a survey method with research subjects as many as 25 students of Class VI SDN Cibala consisting of 12 men and 13 women. The data collection technique used is a test technique. The data that has been obtained is then analyzed by simple statistical analysis. Based on the results of the research that has been done, it can be seen that the ability of KPS in elementary school students of Class VI SDN Cibala as a whole is still low which has an average value of 9.8, while for each aspect of KPS is moderate with a percentage of 54%. Thus, through the results of a survey of the profile of students' science process skills, it is expected that the organized science learning can motivate students to be more creative and innovative